2014
DOI: 10.1007/s11356-014-3784-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of linear alkylbenzene sulfonate on the growth and toxin production of Microcystis aeruginosa isolated from Lake Dianchi

Abstract: The exogenous organic pollutant linear alkylbenzene sulfonate (LAS) pollution and Microcystis bloom are two common phenomena in eutrophic lakes, but the effects of LAS alone on Microcystis remain unclear. In the present study, we investigated the effects of LAS on the growth, photochemical efficiency, and microcystin production of Microcystis aeruginosa in the laboratory. Results showed that low LAS (≤10 mg/L) concentrations improved the growth of M. aeruginosa (12 days of exposure). High LAS (20 mg/L) concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
(62 reference statements)
0
11
1
Order By: Relevance
“…Moreover, extensive biological toxicity could be harmful to terrestrial and aquatic organisms. For example, 0.02 to 1.0 mg/L of linear alkylbenzene sulfonate in water could damage fish gills and high concentration of linear alkylbenzene sulfonate (20 mg/L) inhibited the growth of Microcystis aeruginosa (Moreno-Garrido, Hampel, Lubián, & Blasco, 2001;Wang et al, 2015). Previous researches showed that the anionic surfactants had serious effects on the bioactivity of methanogens, autotrophic ammonia-oxidizing bacteria, and anammox (Brandt, Pedersen, & Sørensen, 2002;Gavala & Ahring, 2002;Qiao, Zheng, Tian, Yu, & Zhou, 2016).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, extensive biological toxicity could be harmful to terrestrial and aquatic organisms. For example, 0.02 to 1.0 mg/L of linear alkylbenzene sulfonate in water could damage fish gills and high concentration of linear alkylbenzene sulfonate (20 mg/L) inhibited the growth of Microcystis aeruginosa (Moreno-Garrido, Hampel, Lubián, & Blasco, 2001;Wang et al, 2015). Previous researches showed that the anionic surfactants had serious effects on the bioactivity of methanogens, autotrophic ammonia-oxidizing bacteria, and anammox (Brandt, Pedersen, & Sørensen, 2002;Gavala & Ahring, 2002;Qiao, Zheng, Tian, Yu, & Zhou, 2016).…”
Section: Research Articlementioning
confidence: 99%
“…Anionic surfactants, a diverse class of chemicals, were designed to have cleaning, solubilization, or sterilization properties and widely used in household cleaning detergents, pesticide formulations, pharmaceuticals, and pulp and paper industries (Olmez‐Hanci, Arslan‐Alaton, & Basar, 2011; Rivera‐Utrilla, Bautista‐Toledo, Sánchez‐Polo, & Méndez‐Díaz, 2012). Concentrations of anionic surfactants reported in surface water and high nitrogen wastewater, such as the water in Dianchi Lake (in China) and washing water, were ranging between 2 and 300 mg/L (Jardak, Drogui, & Daghrir, 2016; Tamiazzo, Breschigliaro, Salvato, & Borin, 2015; Wang et al., 2015). The concentration of anionic surfactants in surface water (above 1 mg/L) could form bubbles and reduce the re‐oxygenation rate and oxygen concentration, resulting in deterioration of water quality (Delforno, Okada, Polizel, Sakamoto, & Varesche, 2012; Huang et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other effects may be on plant physiological and biochemical responses. Some recent studies [82][83][84][85], found that the system of defense and growth of Chara vulgaris L., Lemna minor L., H. dubia (Bl.) Backer and Potamogeton perfoliatus L respectively are affected by Linear Alkylbenzene Sulphonate, (LAS).…”
Section: Znmentioning
confidence: 99%
“…Other effects may be on plant physiological and biochemical responses. Studies by [82], [83], [84] and [85] respectively studied the effect of an organic pollutant (Linear Alkylbenzene Sulphonate, (LAS)) on the defense system and growth of aquatic plants; Chara vulgaris L., Lemna minor L., H. dubia (Bl.) Backer and Potamogeton perfoliatus L respectively.…”
Section: Plantmentioning
confidence: 99%